Dielectric Meta-lattices with Tunable Reflectivity - Suhandoko Dwi Isro; Agoes Soehianie; Alexander Agustinus Iskandar (Institute for Research and Community Services (LPPM) ITB, 2022)
We report a study on the reflective performance of a dielectric meta-lattice formed by a one-dimensional periodic arrangement of silicon nanotubes. It was found that switching from transparent state to reflective state can be done by simply varying one optical parameter of the meta-lattice. The meta-lattice was shown to be capable of providing near-zero and near-unity reflectance at any desired wavelength, even in oblique incidence cases. The results are thus very promising for the development of future optical devices.